CHOICE OF OPTIMAL COMPOSITION OF FEXOFENSDINE GEL WITH ANTI-ALLERGIC EFFECT - Z. D. Khadzhieva; V. A. Chumakova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The prospects of topical formulation development with fexofenadine are conditioned by the possibility of its use in symptomatic, as well as in the combined therapy of allergic reactions on a skin, and the expansion of the pharmaceutical market of antihistamine drugs for external application. The article presents a study of a choice of optimal gel composition with fexofenadine with antiallergic action, we have also substantiated the choice of necessary auxiliary substances.